Effect Of Cause Brand Fit On Brand Loyalty Through Moral Judgment On Aqua Consumers In Surabaya - Adrianto - Trimarjono; Dewi Nuraini (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
This study aims to determine the effect of cause brand fit on brand loyalty and moral judgment. This research was conducted on consumers of AQUA brand drinking water products in the city of Surabaya using purposive sampling technique with the criteria of AQUA mineral water consumers who know the AQUA 1 to 10 social program. To test the hypothesis, the Amos 50 structural model is used. The results show that the cause of brand fit has a significant effect on brand loyalty, moral judgment has no significant effect on the cause of brand fit. Brand loyalty has a significant effect on moral judgment.